Pengaruh Mutu Layanan Terhadap Kepuasan Pemohon SKCK Di Polsek Kota Jombang - Aan Primadonawati; Muhammad Mudjib Musta’in; Supriyanto; Sayekti Suindyah Dwiningwarni (Universitas Darul Ulum, 2018)
Research discussions aim to enhance understanding of customers’ satisfaction in the services of Police Note Information Letter from perspectives of Tangibility, Reliability, Responsiveness, Assurance, and Empathy. Research was take 150 customers sample incidentally. Regression analysis shows that Tangibility, Reliability, Responsiveness, Assurance, and Empathy simultaneously has positive influence on customers’ satisfaction. Empathy partially has no influence on customers’ satisfaction. Research finding will discuss in the context of services quality management